Автоматичне керування потоками електричної енергії розподіленої генерації - Buratynskyi, Ihor (General Energy Institute of the National Academy of Sciences of Ukraine, 2024)
The uninterrupted supply of electricity to consumers and the economic efficiency of the operation of an electric power node with a solar, wind, and reserve power plant, an energy storage system, consumers, and a connection to the power system are achieved by making appropriate decisions about the feasibility of selecting electricity from the power system, which are based on calculations and cost comparison production of electricity with prices of purchase of electricity on the market.